'Pre-Run, Re-Run': An innovative research capacity building exercise. (November 2017) - McAllister, Margaret; Brien, Donna Lee
Abstract: Within higher education it is ironic that experienced and novice researchers rarely take the opportunity to come together to share their research – whether these be to discuss findings, puzzles or developing projects. Within this paper, an innovative strategy building on these assumptions is described. It is entitled: 'Pre-run, Re-run' and is a learning community where specific processes are modelled by all to help build professional communication, collegial respect, and scholarship. Our evaluation showed that there is value in bringing together researchers especially when they have diverse profiles. Also, mixing experience with naivety, by inviting professors and junior staff to fraternize equally, offers the possibility for wide ranging discussion, as well as sharing a range of successful techniques, knowledge of the big picture and ways around obstacles that would otherwise be off-putting for novices. The less experienced perspective can equally be revitalizing because newcomers to scholarship often bring a fresh focus and enthusiasm and energy for practice. While this was a local innovation, which may not be generalizable to all settings, others hoping to bring together disciplines may benefit from utilizing the successful methods to build a productive, mixed research culture.